PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY PADA MATERI SISTEM PENCERNAAN MANUSIA - Alfi Fadhilah; Irvan Permana; Rukmini Handayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Development of augmented reality-based learning media on human digestive system material. This study uses a Research and Development (R&D) approach and the ADDIE model. The aim is to assess the feasibility and effectiveness of the learning media development. The study was conducted at SDN Tenjolaya in the second semester of the 2024/2025 academic year with fifth-grade students as the subjects. Data collection methods included observation, interviews, documentation, validation instrument questionnaires, student and teacher response questionnaires, and question instrument sheets. Expert validation results were as follows: media experts at 98%, language experts at 89.2%, first subject matter experts at 86%, and second subject matter experts at 100%. The student response rate was 98%, and the teacher response rate was 100%. The N-Gain score was 0.74. Based on the results obtained, the augmented reality-based learning media on the human digestive system is suitable and effective for use in the learning process.